An update on renal tubular injury as related to glycolipid metabolism in diabetic kidney disease - Feng, Anqi; Yin, Ruili; Xu, Rong; Zhang, Baoyu; Yang, Longyan (Frontiers in Pharmacology, 2025)
Diabetic kidney disease (DKD) is a severe microvascular complication of diabetes, which can result in end-stage renal disease (ESRD). As the main site of renal reabsorption and its exposed environment, renal tubules can be damaged by various factors. Recent studies have shown that renal tubular epithelial cells (RTECs) injury plays an important role in the occurrence and progression of DKD. The glycolipid metabolism disorders are a vital factor contributing to RTECs injury, which in turn affects the progression of DKD. Abnormal glucose and lipid metabolism can cause oxidative stress, mitochondrial damage, cell apoptosis and lipid accumulation, which can cause RTECs injury. Therefore, this review describes the main pathological mechanism of the injury caused by glycolipid metabolism and the corresponding therapeutic drugs in the clinical treatment of DKD.